Toxicity evaluation of TiO2/MWCNT-CNF hybrid nanocomposites with enhanced photocatalytic activity toward freshwater microalgae: Pseudokirchneriella subcapitata. (March 2022) - Malatjie, Terrence S.; Botha, Tarryn L.; Kuvarega, Alex T.; Madima, Ntakadzeni; de Bruyn, Karin; Tekere, Memory; Nkambule, Thabo T.I.; Mamba, Bhekie B.; Msagati, Titus A.M.
Abstract: A wide range of semiconductor-assisted photocatalytic nanomaterials (NMs) are currently being considered and investigated as potential photocatalysts in water treatment. The applications of nanocomposites composed of nano-structured titania (nano-TiO2 ) and multi-walled carbon nanotubes (MWCNTs) nanocomposites is growing markedly on account of enhanced photocatalytic efficiency. However, concurrent with the increasing production and application comes a serious concern of these emerging nanosystems about their potential risks in aquatic systems, and thereby potentially threatening aquatic organisms via toxic mechanisms that are, at present, poorly understood. In the present study, the lethal toxic effect and oxidative stress induced by TiO2 /MWCNT-CNF nanocomposite in freshwater Pseudokirchneriella subcapitata were assessed . The growth inhibition and sublethal oxidative stress produced by the nanocomposites were evaluated on green microalgae P. subcapitata after 3 days of exposure at 24 h intervals. Moreover, the nanocomposites were physicochemically characterized using a combination of analytical techniques (XRD, SEM/EDS, HRTEM, TGA, UV–Visible spectroscopy). Evaluation of the hybrid for the photocatalytic degradation of Acid Violet 7 dye indicated an enhanced dye removal performance for TiO2 /MWCNT-CNF (96.2%) compared to TiO2 (75.2%) after 2 h of visible light irradiation. While the nanocomposite showed good potential for the degradation of the azo dye, overall, the findings herein indicated that acute exposure of P. subcapitata to various concentrations of TiO2 /MWCNT-CNF nanocomposite may cause algal growth inhibition including undesirable sublethal oxidative stress effects. The findings of this study contribute to a better understanding of the potential hazards of the developing nanocomposites materials towards the nano-bioremediation materials to treat wastewaters. Graphical abstract: Image 1 Highlights: Acute toxicity of photocatalytic nanocomposites with application in water treatment was studied. The photocatalytic performance of TiO2 /MWCNT-CNF was more enhanced than TiO2 NPs with excellent removal efficiency of azo dye. Photocatalytic enhancement of TiO2 /MWCNT-CNF was dependent on surface area. The TiO2 /MWCNT-CNF nanocomposites caused growth inhibition and oxidative stress in algae during 72 h exposure, evidenced by a change in biomarkers activities ( i.e., SOD, GST, and CAT). TiO2 NPs and TiO2 /MWCNT-CNF nanocomposite exhibited agglomeration and concentration-dependent effects on the biomarkers.